2022
DOI: 10.3390/ijms232112966
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Leaf Morphology and Related Gene Expression between Diploid and Tetraploid Birch (Betula pendula)

Abstract: Plant polyploidization changes its leaf morphology and leaf development patterns. Understanding changes in leaf morphology and development patterns is a prerequisite and key to studying leaf development in polyploid plants. In this study, we quantified and analyzed the differences in leaf morphology, leaf growth polarity, and leaf size between diploid and tetraploid birches (Betula pendula subsp. pendula), and preliminarily investigated genes involved in leaf growth and development in birch. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Smaller plant sizes in tetraploid than diploid were also reported in Triticum monococcum and apples [35][36][37]. Slower growth with short but thick stems and large leaves was reported in autotetraploid britch, poplus, and eucalyptus tree species [3,38,39]. Ren et al [40], Corneillie et al [33], and Rosellini et al [41] described this shorter but thicker stem as being due to shorter but wider cells in tetraploid compared to its diploid counterpart.…”
Section: Discussionmentioning
confidence: 88%
“…Smaller plant sizes in tetraploid than diploid were also reported in Triticum monococcum and apples [35][36][37]. Slower growth with short but thick stems and large leaves was reported in autotetraploid britch, poplus, and eucalyptus tree species [3,38,39]. Ren et al [40], Corneillie et al [33], and Rosellini et al [41] described this shorter but thicker stem as being due to shorter but wider cells in tetraploid compared to its diploid counterpart.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, leaf color, wax layer thickness, leaf hair density, and sugarcane leaf thickness are influenced by the clones used [29], [30]. Differences in leaf morphology cause differences in the amount of light received, reflected, and absorbed by the leaves [30]- [35]. Such conditions cause the Fv/Fo, Vj, PI, and Mo values produced by each sugarcane clone to differ in the stem elongation and maturity phases.…”
Section: B Ojip Variablesmentioning
confidence: 99%
“…Some species have been further explored for the possible causes of polyploid leaf changes. Cytology and gene expression analyses revealed that the leaf magnification of the Betula pendula tetraploid was related to cell expansion rather than cell number [39]. Thus, investigating the phenotypic variation of S. pohuashanensis tetraploids, especially leaf morphology, can help us better understand the variation in plant characteristics caused by polyploidization.…”
Section: Introductionmentioning
confidence: 99%